An image sensor which captures 100 consecutive frames at 1000000 frames - Etoh, T.G.
An image sensor for a video camera of 1000000 frames per second (fps) was developed. The specifications of the developed sensor are as follows: 1) frame rate: 1000000 fps; 2) pixel count: 81 120 (=312×260) pixels; 3) total number of successive frames: 103 frames; 4) gray levels: 10 b; and 5) open area of each pixel (fill factor): 580 square micrometers (13%). The overwriting function is installed for synchronization of image capturing with occurrence of the target event. Sensitivity is significantly high with the large photogate. Some innovative technologies were introduced to achieve ultrahigh performance, including slanted linear CCD in situ storage, curving design procedure, and a CCD switch with fewer metal shunting wires. They are applicable to the development of other new high-performance image sensors.
Keywords: 260 pixel; 312 pixel; 81120 pixel; CCD switch; Consecutive frames; Curving design procedure; Frame rate; Gray levels; Image sensor; Open area; Photogate; Slanted linear CCD; Synchronization; Video camera